2008
DOI: 10.1002/ejic.200701051
|View full text |Cite
|
Sign up to set email alerts
|

A Brave New World: The Heteroatom Chemistry of 1,3,2,4‐Benzodithiadiazines and Related Compounds

Abstract: This review highlights the most important advances in the heteroatom chemistry of 1,3,2,4-benzodithiadiazines (π-excessive and formally antiaromatic heterocycles), covering methods for synthesis, nontrivial features of the molecular and π-electronic structure, spectral properties, and reactivity, in particular the transformations into persistent π-radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 164 publications
0
12
0
Order By: Relevance
“…Reactions required higher temperatures but even at 20°C P(OPh) 3 interacted with both hydrocarbon 1b and fluorocarbon 1c derivatives very slowly to give after several days complex reaction mixtures in which only XP(OPh) 3 (X = S, O, in proportion 1:1 and 1:2.3, respectively) were identified by 13 С and 31 Р NMR and GC‐MS techniques (Scheme ). In the case of X = S, initial compounds 1 were obviously the source of sulfur (desulfurization of sulfur–nitrogen rings, cages, and chains by PR 3 compounds is well known [c]), whereas with X = O a source of oxygen is not entirely clear. The experiments were performed under argon, but their duration was 12–15 days; and atmospheric oxygen might enter the reaction systems to oxidize P(OPh) 3 into OP(OPh) 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reactions required higher temperatures but even at 20°C P(OPh) 3 interacted with both hydrocarbon 1b and fluorocarbon 1c derivatives very slowly to give after several days complex reaction mixtures in which only XP(OPh) 3 (X = S, O, in proportion 1:1 and 1:2.3, respectively) were identified by 13 С and 31 Р NMR and GC‐MS techniques (Scheme ). In the case of X = S, initial compounds 1 were obviously the source of sulfur (desulfurization of sulfur–nitrogen rings, cages, and chains by PR 3 compounds is well known [c]), whereas with X = O a source of oxygen is not entirely clear. The experiments were performed under argon, but their duration was 12–15 days; and atmospheric oxygen might enter the reaction systems to oxidize P(OPh) 3 into OP(OPh) 3 .…”
Section: Resultsmentioning
confidence: 99%
“…1,3,2,4‐Benzodithiadiazines ( 1 , Chart ) represent a relatively rare class of compounds possessing formal features of antiaromaticity in combination with moderate thermal stability. Their heteroatom reactivity is of obvious fundamental interest . Particularly, it was found that 1,3,2,4‐benzodithiadiazine and its derivatives, including low‐ and high‐fluorinated ones (as well as 1‐Se congener of trifluoro derivative) react with PPh 3 (Ph = C 6 H 5 ) to give chiral 1,2,3‐benzodithiazol‐2‐yl iminophosphoranes ( 2 , Chart ) inaccessible by other approaches including classical Kirsanov and Staudinger reactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DFT approach at the (U)B3LYP/6‐31+G(d)39, 40 level of theory was used for the calculations since it performs well for molecular structures and properties of main‐group compounds including electron affinities and hyperfine coupling constants 20, 41, 42. Previously, the (U)B3LYP method was successfully employed to reproduce the properties of a series of both closed‐ and open‐shell chalcogen–nitrogen cycles and cages including RAs 25–31, 43–50. Quantum chemical calculations on RAs and their neutral precursors were carried out with full geometry optimization using the GAMESS51 and GAUSSIAN‐0352 programs.…”
Section: Methodsmentioning
confidence: 99%
“…It was first observed with thermolysis of 1,3,2,4‐benzodithiadiazines (Scheme ) within the study of the reactivity of those 12π‐electron, i. e . formally antiaromatic, heterocycles . Then it was found that synthetically it is much more convenient to generate the radicals by reduction of 1,2,3‐dithiazoliums under conditions favorable for the radicals self‐condensation .…”
Section: Synthesismentioning
confidence: 99%